Iranian EFL and Malaysian ESL University Students’ Use of Language Learning Strategies - Sara Kashefian-Naeeini; Nooreiny Maarof (Universitas Islam Negeri Walisongo Semarang, 2022)
In recent years, more active roles have been allocated to language learners. Empowering students can help them function more autonomously and their ability to make appropriate use of language learner strategies (LLSs) predisposes them to achieve their academic goals. The participants of the present study were male and female undergraduate university students from two different countries. A multivariate analysis of variance was conducted to compare the use of the six strategy categories of memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies together with direct strategies, indirect strategies and overall use of language learning strategies among Iranian EFL and Malaysian ESL university students. It was illuminated that social context influenced selected students’ use of social strategies. Classroom observations helped the researchers to find out about frequency of use of language learning strategies. Metacognitive and cognitive strategies were the most used in-class strategies among Iranian and Malaysian university students, respectively. It is suggested that instructors provide a wide range of language learning strategies to satisfy the needs of learners with different needs and expectations.